STABILITY OF THE TRANSGENE REPORTER FOR OSTEOBLASTS IN THE TRANSGENIC COL10A1:NLGFP MEDAKA FISH (ORYZIAS LATIPES) - Tô Thanh, Thúy; Nguyen, Thi Thu Ha, Nguyen Tuong Anh, Ha Thi Minh Tam, Nguyen Huy Manh, Tran Thi Thuy Chinh, Tran Duc Long (Tạp chí Sinh lý học Việt Nam, 2022)
Objective: to examine genetic and functional stability of an osteoblast reporter transgene coding for green fluorescence protein (GFP) in the transgenic col10a1:nlGFP fish generated a decade ago. Methods: homozygous and hemizygous fish for the transgene GFP were segregated by testcrossing. PCR were performed to check for the presence of the transgene GFP in the homozygous and hemizygous genomes. GFP signal was used to assess distribution of collagen10a1 expressing osteoblasts. Alizarin complexone (ALC) was used to visualize mineralized matrix of the live larvae. Expression pattern of the transgene GFP and level of bone mineralization in the live transgenic fish was analyzed using fluorescent imaging and ImageJ analysis for GFP and ALC signal, respectively. Results: three homozygous col10a1:nlGFP fish were found and many hemizygotes were produced. Both homozygous and hemizygous fish still contain the transgene GFP in their genomes and express GFP in a pattern recapitulating endogenous collagen10a1 gene expression in osteoblast. They also retain the pattern of GFP expression in bone structures like that of the original transgenic fish generated a decade ago. This confirms the genomic and functional stability of the transgene GFP in the fish